Biogas Alternative Soursce of Energy for Republic of Moldova - Alina CRACIUN; Tatiana CHIRIL; Gheorghe Adrian ZUGRAVU (Communications of International Proceedings, 2023)
The paper presents several aspects related to the production ofbiogas from vegetable demerara and sludge resulting in wastewater treatment plants.The history of biogas production, the legislation in force, as well as the principles of the biogasprocessare presented.At the end of the workthere are several economic advantages and environmental protection by processing organic waste to obtain biogas.
Keywords: alternative sources of energy; obtaining and utilizing biogas